Odpowiedź :
Odpowiedź:
[tex]\begin{cases}5x-2y=10 \\ -3x-4y=1\end{cases}[/tex]
[tex]\begin{cases}5x=2y+10 \\ -4y-3x=1 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ -4y-3x=1 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ -4y-3(\frac{2}{5}y+2)=1 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ -4y-\frac{6}{5}y-6=1 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ -\frac{26}{5}y-6=1 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ -\frac{26}{5}y=7 \end{cases}[/tex]
[tex]\begin{cases} x=\frac{2}{5}y+2 \\ y=-\frac{35}{26} \end{cases}[/tex]
[tex]\begin{cases} x=-\frac{70}{130}+2 \\ y=-\frac{35}{26} \end{cases}[/tex]
[tex]\begin{cases} x=\frac{19}{13} \\ y=-\frac{35}{26} \end{cases}[/tex]
Odpowiedź:
[tex]\begin{cases}5x-2y=10\ \ |\cdot(-2)\\-3x-4y=1\end{cases}\\\\\\+\begin{cases}-10x+4y=-20\\-3x-4y=1\end{cases}\\----------\\-13x=-19\ \ |:(-13)\\\\x=\frac{19}{13}\\\\\\-3\cdot\frac{19}{13}-4y=1\\\\-\frac{57}{13}-4y=1\\\\-4y=1+\frac{57}{13}\\\\-4y=\frac{13}{13}+\frac{57}{13}\\\\-4y=\frac{70}{13}\ \ |:(-4)\\\\y=\frac{\not70^3^5}{13}\cdot(-\frac{1}{\not4_{2}})\\\\y=-\frac{35}{26}[/tex]
[tex]\begin{cases}x=\frac{19}{13}\\y=-\frac{35}{26}\end{cases}[/tex]